Accessibility and Use of Internet Facilities in University Libraries: A Study of Federal University of Petroleum Resources, Effurun - Ferdinand, Omosekejimi Ademola; Ijiekhuamhen , Osaze Patrick; Emuejevoke , Paul Ogo (MiddleBelt Journal of Library and Information Science, 2016)
This study is to examine the availability of Internet services in Federal University of Petroleum Resources, Effurun FUPRE library. The total population for this study comprises of 2,850 students and staff of FUPRE among which are 1,890 students, 540 academic staff and 420 non academic staff. A total sample size of 285 was drawn from the total population using the purposive sampling technique and questionnaire was used for data collection. Findings of the study revealed among others that though the Internet facilities available in FUPRE library are functional and accessible to the students and staff of the institution, they are irregular and inconsistent in terms of availability and as such do not satisfy them; staff and students make use of the Internet facilities when available for accessing newly published materials online, for study purpose, research and academic development and gathering recently published information materials for project work. The following among others were suggested to improve on the accessibility and use of Internet facilities in academic libraries: Government and university management should increase the yearly allocation of the library so that they can subscribe to reliable high speed internet service providers that will allow users to enjoy full Internet service, more bandwidths should be sought so as to provide faster access that will save much of the users’ time and be a source of motivation to users and the computer systems acquired for the library should be recent models and the telecommunication facilities should be high-speed models